Teenage Promiscuity's Effect On Early Marriage - Aprilia, Salsa; Achdiani, Yani; Arlianty, Lia Shafira (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2024)
Teenage promiscuity in early marriage is very influential, many teenagers apply for marriage dispensation because they are pregnant outside of marriage. The purpose of this study is to determine the impact, factors, and efforts to prevent adolescents aged 13 to 18 years from engaging in promiscuity until marriage occurs at an early age. This research method is a literature study. The results of the study show the impact, factors, and prevention efforts of adolescent promiscuity in early marriage committed by adolescents aged 13 to 18 years. Factors of promiscuity in early marriage are peer influence, environment, lack of sexual education and knowledge, influence of social media, family, and economic problems. The impact of promiscuity in early marriage is reproductive health, risk of maternal mortality, and psychological impact. It can be concluded that the average teenager from the age of 13 to 18 years old engages in promiscuity because of supporting factors, causing adolescents to fall into promiscuity until they finally have sexual intercourse with the opposite sex and end up pregnant outside of marriage which requires the teenager to marry at an early age, without knowing the very high impact on early marriage. The impact of teenage promiscuity in early marriage such as reproductive health impacts, risk of maternal mortality, and psychological impacts. Efforts to prevent promiscuity in early marriage are by participating in positive activities such as participating in the generation planning programme (GenRe). Suggestions are expected to parents when children are at a vulnerable age, higher knowledge is needed to know the negative impacts of promiscuity committed by adolescents, sexual education in adolescents is very important to provide accurate and comprehensive information about reproductive health, sexuality, and the consequences of risky behaviour.